BUSINESS INCUBATOR IN HIGHER EDUCATION FOR STUDENTS BUSINESS OWNER (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Entrepreneurship Development Program in Higher Education is conducted in the form of Student Business Incubator which is a program with mission to produce independent entrepreneur based on science and technology, through an integrated program involving lecturers managing Incubators, Resources, Companies and Institutional entrepreneurship off campus. Student Business Incubator Activities include: development of entrepreneurial spirit, management training and business skills for tenants, business consulting, review in established companies and facilitating tenants in entrepreneurship to produce new entrepreneurs. Tenant establishes and enhances the skills to support the management and marketing of products in laboratories at the universities that have been prepared. To expand the insight and marketing network. The purpose of this study is to evaluate the activities of Entrepreneurial Development Program in the form of Business Incubator at the University of Merdeka Malang which aims to foster students to pioneer and establish businesses that cover the business: culinary, crafts, services, and information technology . The research was conducted by qualitative descriptive method. The sample of the research is the students who attended the Entrepreneurial Development Program at University of Merdeka Malang, which are 20 students each in 2016 and 2017. The primary data were obtained from the interviews of the 47 tenant incubator and activity documentation. University of Merdeka Malang Business Incubator.